Evaluating the efficacy of UNav: A computer vision-based navigation aid for persons with blindness or low vision. - Yang, Anbang; Tamkittikhun, Nattachart; Hamilton-Fletcher, Giles; Ramdhanie, Vinay; Vu, Thu; Beheshti, Mahya; Hudson, Todd; Vedanthan, Rajesh; Riewpaiboon, Wachara; Mongkolwat, Pattanasak; Feng, Chen; Rizzo, John-Ross (Assistive Technology, 2025)
UNav is a computer-vision-based localization and navigation aid that provides step-by-step route instructions to reach selected destinations without any infrastructure in both indoor and outdoor environments. Despite the initial literature highlighting UNav's potential, clinical efficacy has not yet been rigorously evaluated. Herein, we assess UNav against standard in-person travel directions (SIPTD) for persons with blindness or low vision (PBLV) in an ecologically valid environment using a non-inferiority design. Twenty BLV subjects (age = 38 ± 8.4; nine females) were recruited and asked to navigate to a variety of destinations, over short-range distances (<200 m), in unfamiliar spaces, using either UNav or SIPTD. Navigation performance was assessed with nine dependent variables to assess travel confidence, as well as spatial and temporal performances, including path efficiency, total time, and wrong turns. The results suggest that UNav is not only non-inferior to the standard-of-care in wayfinding (SIPTD) but also superior on 8 out of 9 metrics, as compared to SIPTD. This study highlights the range of benefits computer vision-based aids provide to PBLV in short-range navigation and provides key insights into how users benefit from this systematic form of computer-aided guidance, demonstrating transformative promise for educational attainment, gainful employment, and recreational participation.